SISTEM INFORMASI PENCARIAN JASA TUKANG BANGUNAN - Polapa, Risman; Abas, Mohamad Ilyas; Handayani, Tri Pratiwi; Lasarudin, Alter (Jurnal Ilmu Komputer (JUIK), 2024)
This research aims to design a Web-based Building Services Search Information System and implement a Web-Based Building Builder Services Search Information System. This research was developed using the Rapid Application Development (RAD) method. In RAD, users and analysts participate in three stages. The three stages are implementation, RAD design and requirements planning. With these stages, the application of the RAD method is very appropriate and suitable for developing website-based systems. The results of this research were that the researcher had previously conducted an interview with one of the head builders. Craftsmen in their profession as builders are to get work that suits their skills, only certain people know and understand the workman's performance, what field the craftsman is skilled in, so if there is a special job that must be done by a craftsman that suits his skills. So the employer must meet the craftsman directly and ask about the craftsman's skills. Conclusion: We have succeeded in designing a web-based information system for searching for construction services, able to make it easier for customers (employers) to search for construction services according to the skills required by customers (employers), as well as making it easier for builders to find work that suits the craftsman's skills. With this information system, it can help builders and customers (employers) in the process of searching for builders according to their expertise in the form of the Web or other web browsers.